Brand Marketing Communications Micro, Small and Medium Enterprises (SMEs) in Indonesia (Resonance Pyramid Brand Implementation Study on Radio Magno) - Satria, H W (KnE Social Sciences, 2018)
This research focused on assessing brand marketing communication of Magno Radio using the approach of two models of Integrated Marketing Communication (IMC) and Customer-based Brand Equity (CBBE). It used descriptive qualitative approach with case study method using key informants Managing Director of Magno Radio. The unit of analysis of this research is based on the perspective of sender, namely the owner of Magno Radio, while data sources were obtained through interviews, observation, and secondary data. Results of this study illustrate how the IMC and CBBE can help establish brand equity of Magno Radio in export markets, particularly in Japan. It is also expected to contribute further study and enrich the study of brand equity in the field of applied science communication. Practically, this research can be applied in general by Indonesian SMEs in planning their brands with the aim to penetrate the export market. Keywords: IMC, CBBE, brand communication, SMEs